2018
DOI: 10.1007/s10230-018-0511-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electromagnetic Wave Sensors with Optical and Low-frequency Spectroscopy Methods for Real-time Monitoring of Lead Concentrations in Mine Water

Abstract: The feasibility of using novel electromagnetic wave sensors for real-time monitoring of metal pollution in water was assessed. Five solutions with different concentrations of lead (0, 1, 10, 50, 100 mg/L) were measured using several sensing methods: UV-Vis spectroscopy, low frequency capacitance and resistance measurements, and two sensing systems based on microwave technology. With this last approach, two sensing devices were used: a resonant cavity and a planar sensor with gold interdigitated electrode desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…During the last few years, several planar microwave sensors with different conformations have been developed and tested for differentiate compositions of water for both qualitative and quantitative concentration measurements [ 49 , 50 , 51 , 52 , 53 ]. Between planar sensing structures, Korostynska et al [ 49 ] confirmed the action of a novel planar sensor with a sensing element consisted of interdigitated electrodes (IDE, also defined as interdigital by other researchers) metal patterns (silver, gold and/or copper) for water analysis observing changes in the microwave part of the EM spectrum analysing 20 µL of deionized water (DIW), KCl, NaCl and MnCl at various concentrations ( Figure 9 a,b).…”
Section: Functionalised Electromagnetic Wave Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few years, several planar microwave sensors with different conformations have been developed and tested for differentiate compositions of water for both qualitative and quantitative concentration measurements [ 49 , 50 , 51 , 52 , 53 ]. Between planar sensing structures, Korostynska et al [ 49 ] confirmed the action of a novel planar sensor with a sensing element consisted of interdigitated electrodes (IDE, also defined as interdigital by other researchers) metal patterns (silver, gold and/or copper) for water analysis observing changes in the microwave part of the EM spectrum analysing 20 µL of deionized water (DIW), KCl, NaCl and MnCl at various concentrations ( Figure 9 a,b).…”
Section: Functionalised Electromagnetic Wave Sensorsmentioning
confidence: 99%
“…Between planar sensing structures, Korostynska et al [ 49 ] confirmed the action of a novel planar sensor with a sensing element consisted of interdigitated electrodes (IDE, also defined as interdigital by other researchers) metal patterns (silver, gold and/or copper) for water analysis observing changes in the microwave part of the EM spectrum analysing 20 µL of deionized water (DIW), KCl, NaCl and MnCl at various concentrations ( Figure 9 a,b). Then, Mason et al [ 50 ], Moejes et al [ 51 ] and Frau et al [ 52 ] demonstrated the ability to detect respectively Lincomycin and Tylosin antibiotics, Tetraselmis suecica and lead ions (Pb 2+ ) using gold (Au) eight-pair IDE sensors.…”
Section: Functionalised Electromagnetic Wave Sensorsmentioning
confidence: 99%
“…spectroscopy could be used physically to separate electromagnetic waves of various frequencies [13,14]. erefore, it generates a spectrum which shows the constituents' frequencies [15,16].…”
Section: Spectroscopy a Characterization Technique Known Asmentioning
confidence: 99%
“…Current research has demonstrated the possibility to determine the presence and concentration of specific components and pollutants in water, e.g. lead ions (Pb 2+ ) (Frau et al 2018a), sugars (Harnsoongnoen et al 2018), nitrates (Cashman et al 2017), phosphate (Nag et al 2019), antibiotics (Mason et al 2018), silver materials (Ateeq et al 2017), water in fuel (Andria et al 2019), marine algae (Moejes et al 2018), liquid mixtures, as acetone and water (Wei et al 2018), ethanol and water Wiltshire and Zarifi 2018).…”
Section: Microwave Technology and Watermentioning
confidence: 99%